MANAJEMEN PROGRAM TAHFIDZUL QUR’AN DI BOARDING SCHOOL MAN BLORA - Nila Himatul Ulya; M. Rikza Chamami (Berajah Journal, 2026)
The decline in student interest in participating in the Qur’an memorization program at the MAN Blora Boarding School is the background of this research. The goal is to formulate a development strategy for the MAN Blora Boarding School so that it can produce graduates who are not only intellectually intelligent but also have a strong understanding of religion in facing the changing times. The management of the Qur’an memorization program determines student interest in the success of the Qur’an memorization program in the future. This research is a qualitative field research. Data sources in this study were obtained through interviews with the Principal, Chairperson, tahfidz mentors, administrators, and tahfidz students of the MAN Blora Boarding School, in addition to conducting observations and documentation in data collection. Data analysis was carried out by reducing data, presenting data, and drawing conclusions. The results of this study indicate that the MAN Blora Boarding School has implemented management functions systematically in implementing the Qur’an memorization program, starting from planning, organizing, implementing, to controlling. The implementation of these management functions has proven to produce students who are able to exceed the memorization targets that have been previously set, so that the MAN Blora Boarding School has succeeded in achieving its goals and targets optimally.